2019
DOI: 10.1088/1757-899x/691/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Design and Development of Free Piston Linear Generators in Hybrid Vehicles

Abstract: The rapid exploitation of fossil fuels due to their indiscriminate use has brought us to a situation when we cannot sustain the use of fuels like petrol and diesel for more than 30 years from now. Governments and energy companies around the world are looking for some alternative source of energy to power the vehicles. A lot of research is being carried out in this field and many researchers have concluded that hybrid vehicles can be a boon to eradicating the dependence on conventional fuels and move towards ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, FPLGs are still early in the experimental phase and have not been tested on a commercial scale. Some issues with them include detent force, inconsistent start, combustion, misfiring, and lubrication [39].…”
Section: Definitions Mechanisms and Pros And Consmentioning
confidence: 99%
See 1 more Smart Citation
“…However, FPLGs are still early in the experimental phase and have not been tested on a commercial scale. Some issues with them include detent force, inconsistent start, combustion, misfiring, and lubrication [39].…”
Section: Definitions Mechanisms and Pros And Consmentioning
confidence: 99%
“…The authors outlined the process the DLR followed and indicated that best results were found when the subsystems are built separately, hence, less reliant on each other, and then assembled. Rathore et al [39] explored FPLG as a whole and by its subsystems. The authors reviewed different types of FPLGs based on piston arrangements.…”
Section: Recent Research Developmentsmentioning
confidence: 99%
“…The inputs were similar to the initial design points and the outputs were maximum equivalent stress and resonant frequency. The NN algorithm was then trained based on these inputs and then outputs were calculated to determine the weight functions of the hidden layers associated with the neurons [45]. For the flexure springs for highspeed and high-stroke applications, the most common materials are steel and titanium alloys.…”
Section: Design Optimization and Sensitivity Analysismentioning
confidence: 99%